Sidoarjo Mud: A Potential Cement Replacement Material - Nuruddin M.F.; Bayuaji R.; Masilamani M.B.; Biyanto T.R. (Institute of Research and Community Outreach - Petra Christian University, 2010)
This paper presents an experimental and analytical research conducted to study the properties of mortar when treated Sidoarjo mud was added into the mix replacing partially the cement content. The replacements were done at 0, 5, 10, 15, and 20%. Compression, tensile, porosity and Ultrasonic Pulse Velocity (UPV) tests were conducted to evaluate the effect of Sidoarjo mud in mortar. Analyses on the mud were also conducted through X-ray diffraction (XRD), X-ray Fluorescence (XRF), and scanning electron microscope with an energy dispersive X-ray analysis system (SEM-EDX). The results showed that the mud could be used as a cementitious material with optimum ordinary Portland cement (OPC) replacement at 10%.